Numerical study of dispersed oil–water turbulent flow in horizontal tube - Walvekar, Rashmi G.; Choong, Thomas Shean Yaw; Hussain, Siti Aslina; Mohammad Khalid,; Chuah, Teong Guan (Elsevier, 2009)
In this paper, the three-dimensional flow of two immiscible liquids in a horizontal pipe has been investigated numerically. The transient numerical simulations of two-phase dispersed flow in a pipe (of ID = 0.0024 m) have been carried out using commercial CFD package FLUENT 6.2 in conjunction with multiphase model. Oil–water system is selected as the two-phase system in this work. The k − ε model was used to describe the turbulence in continuous phase. The numerical results in terms of the phase distribution profiles and average in-situ hold-up are presented and discussed. The predicted results are seen to be in good agreement qualitatively as well as quantitatively with the previous experimental results available in the literature